Hyperprolactinemic African elephant (Loxodonta africana) females exhibit elevated dopamine, oxytocin and serotonin concentrations compared to normal cycling and noncycling, low prolactin elephants†. Issue 6 (8th March 2019) - Prado, Natalia A; Keady, Mia; Oestmann, Alexa; Steinbeiser, Cathleen M; Brown, Janine L
Abstract: Many zoo elephants do not cycle normally, and for African elephants, it is often associated with hyperprolactinemia. Dopamine agonists successfully treat hyperprolactinemia-induced ovarian dysfunction in women, but not elephants. The objective of this study was to determine how longitudinal dopamine, serotonin, and oxytocin patterns in African elephants are related to ovarian cycle function. We hypothesized that dopamine concentrations are decreased, while oxytocin and serotonin are increased in non-cycling, hyperprolactinemic African elephants. Weekly urine and serum samples were collected for eight consecutive months from 28 female African elephants. Females were categorized as follows: (1) non-cycling with average prolactin concentrations of 15 ng/ml or greater (HIGH; n = 7); (2) non-cycling with average prolactin concentrations below 15 ng/ml (LOW; n = 13); and (3) cycling with normal progestagen and prolactin patterns (CYCLING; n = 8). Both oxytocin and serotonin were elevated in hyperprolactinemic elephants. Thus, we propose that stimulatory factors may play a role in the observed hyperprolactinemia in this species. Interestingly, rather than being reduced as hypothesized, urinary dopamine was elevated in hyperprolactinemic elephants compared to CYCLING and LOW prolactin groups. Despite its apparent lack of regulatory control over prolactin, this new evidence suggests that dopamine synthesis and secretion are not impaired in these elephants, and perhaps are augmented. Abstract : Dopamine production is not impaired in hyperprolactinemic elephants as previously thought and perhaps augmented.